Meta-Analisis Prediktor School Well-Being pada Siswa SMA di Indonesia - Abdulloh Hadziq; M. Ali Najich; I’in Khalimatus Sa’diyah (Universitas Negeri Malang, 2026)
School well-being is an essential pillar for the psychological and academic development of adolescents; however, previous findings regarding the strength of its predictors remain inconsistent. This study aims to evaluate the combined effect size of predictors (internal and external) on school well-being among high school students in Indonesia, as well as to test the moderating effects of the COVID-19 pandemic period and year of publication. Using a meta-analytic approach, data were aggregated from 19 primary studies that met the inclusion criteria. The results of the quantitative synthesis indicate a significant positive correlation at a moderate level between the sum of predictors and the level of school well-being (r=0.41; p<0.000). Although very high between-study heterogeneity was identified (I² = 82.29%), moderator testing demonstrated that the pandemic period and publication year trends did not significantly moderate the strength of this correlation. The absence of these moderating effects does not necessarily indicate absolute resilience of the construct against crises, but rather suggests that the fulfillment of internal resources and external support remains an essential prerequisite consistently required across changing times. Furthermore, the Trim and Fill analysis confirmed the absence of publication bias. These findings underscore the importance of integrating social-ecological support and strengthening individual psychological resources in the formulation of comprehensive education policies. Abstrak Kesejahteraan sekolah (school well-being) merupakan pilar esensial bagi perkembangan psikologis dan akademik remaja, namun temuan terdahulu mengenai kekuatan prediktornya masih menunjukkan inkonsistensi. Penelitian ini bertujuan untuk mengevaluasi ukuran efek gabungan (combined effect size) dari prediktor (internal dan eksternal) terhadap school well-being pada siswa Sekolah Menengah Atas (SMA) atau sederajat di Indonesia, serta menguji efek moderator berupa periodisasi pandemi COVID-19 dan tahun publikasi. Melalui pendekatan meta-analisis, data diagregasi dari 19 studi primer yang memenuhi kriteria inklusi. Hasil sintesis kuantitatif menunjukkan adanya korelasi positif yang signifikan pada level moderat antara akumulasi prediktor dengan tingkat school well-being (r=0,41; p<0,000). Meskipun teridentifikasi heterogenitas antar-studi yang sangat tinggi (I2=82,29%), pengujian moderator membuktikan bahwa periodisasi pandemi dan tren waktu publikasi tidak memoderasi kekuatan korelasi tersebut secara signifikan. Ketiadaan efek moderasi ini tidak serta-merta menunjukkan ketangguhan (resilience) mutlak konstruk terhadap krisis, melainkan mengindikasikan bahwa pemenuhan sumber daya internal dan dukungan eksternal tetap menjadi prasyarat esensial yang konsisten dibutuhkan melintasi perubahan waktu. Lebih lanjut, analisis Trim and Fill mengonfirmasi tidak adanya bias publikasi. Temuan ini menegaskan pentingnya integrasi dukungan ekologi sosial dan penguatan sumber daya psikologis individu dalam perumusan kebijakan pendidikan yang komprehensif.